A threat from both sides: Multiple introductions of genetically distinct H5 HPAI viruses into Canada via both East Asia-Australasia/Pacific and Atlantic flyways. Issue 2 (25th August 2022) - Alkie, Tamiru N; Lopes, Sara; Hisanaga, Tamiko; Xu, Wanhong; Suderman, Matthew; Koziuk, Janice; Fisher, Mathew; Redford, Tony; Lung, Oliver; Joseph, Tomy; Himsworth, Chelsea G; Brown, Ian H; et al.
Abstract: From 2016 to 2020, high pathogenicity avian influenza (HPAI) H5 viruses circulated in Asia, Europe, and Africa, causing waves of infections and the deaths of millions of wild and domestic birds and presenting a zoonotic risk. In late 2021, H5N1 HPAI viruses were isolated from poultry in Canada and also retrospectively from a great black-backed gull ( Larus marinus ), raising concerns that the spread of these viruses to North America was mediated by migratory wild bird populations. In February and April 2022, H5N1 HPAI viruses were isolated from a bald eagle ( Haliaeetus leucocephalus ) and broiler chickens in British Columbia, Canada. Phylogenetic analysis showed that the virus from bald eagle was genetically related to H5N1 HPAI virus isolated in Hokkaido, Japan, in January 2022. The virus identified from broiler chickens was a reassortant H5N1 HPAI virus with unique constellation genome segments containing PB2 and NP from North American lineage LPAI viruses, and the remaining gene segments were genetically related to the original Newfoundland-like H5N1 HPAI viruses detected in November and December 2021 in Canada. This is the first report of H5 HPAI viruses' introduction to North America from the Pacific and the North Atlantic-linked flyways and highlights the expanding risk of genetically distinct virus introductions from different geographical locations and the potential for local reassortment with both the American lineage LPAI viruses in wild birds and with both Asian-like and European-like H5 HPAI viruses. We also report the presence of some amino acid substitutions across each segment that might contribute to the replicative efficiency of these viruses in mammalian host, evade adaptive immunity, and pose a potential zoonotic risk.